If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -85 = 123 + -3x Reorder the terms: -85 + 5x = 123 + -3x Solving -85 + 5x = 123 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -85 + 5x + 3x = 123 + -3x + 3x Combine like terms: 5x + 3x = 8x -85 + 8x = 123 + -3x + 3x Combine like terms: -3x + 3x = 0 -85 + 8x = 123 + 0 -85 + 8x = 123 Add '85' to each side of the equation. -85 + 85 + 8x = 123 + 85 Combine like terms: -85 + 85 = 0 0 + 8x = 123 + 85 8x = 123 + 85 Combine like terms: 123 + 85 = 208 8x = 208 Divide each side by '8'. x = 26 Simplifying x = 26
| -14+10x=18+8x | | -4(x-8)=-20 | | 3/5=x/22 | | 3(5x-7)=25 | | 2x+4+6=x+14+1 | | 4x^2-16x+2.5=0 | | 8/9(x-1)=16 | | -3(x-5)-30=3 | | 8(2x+5)=6(x+10) | | n=r/2 | | 5(12x+2)=60x-3 | | 1.8+2.8=2.5+21 | | 8k^2+1=65 | | 7(3y-2)-(9y+5)= | | -30-10x=-12x+28 | | 3/10x=-15 | | -6=-(x-20) | | 12=-6-3/4x | | cosx=-0.09 | | 28x=7(10-x) | | 9x^2-5=31 | | 5y+3y=34-2 | | -7x-96=x-32 | | 27=-3x-5-5x | | 4x^2-36x-4=0 | | 10=2(x+2) | | (3a-2)x-a+3=x+8 | | -3v+6v=9+12 | | 12+6y=-6y | | V+13=8 | | 24=6/18-16-14 | | 7+4x=6x+3 |